Development of the Performance of Multicast Routing Protocols in MANET Using PUMA Protocol - بدر, يعرب; سعيد, علا (Latakia University Journal -Engineering Sciences Series, 2021)
Data traffic between nodes in a network vary from unicast (one-to-one) to broadcast (one-to-all). Between these two types there is also multicast either (one-to-many) or (many-to-many). Multicast is a compromise between the unicast، which is easy and the broadcast that drowns the network with excess packets. Protocol PUMA (Protocol for Unified Multicasting Through Announcements) depend on mesh-based selects one node as a core node and informs other nodes within MANET network. PUMA that combines several receiving nodes together and provides several paths to reach the target nodes. In this paper, we are carrying out simulations using NS2 assuming different scenarios and different speeds of mobile nodes. We collect results, process and verify performance parameters such as delay, throughput and packet delivery ratio. Showing that how to improve routing performance in the proposed scenarios.